How does measurement of platelet P-selectin compare with other methods of measuring platelet function as a means of determining the effectiveness of antiplatelet therapy?. (3rd April 2019) - Fox, Susan C.; May, Jane A.; Dovlatova, Natalia; Glenn, Jackie R.; Johnson, Andrew; White, Ann E.; Radhakrishnan, Ashwin; Heptinstall, Stan
Abstract: Measurement of P-selectin on activated platelets as a means of measuring platelet function utilizing the technology described here has the advantage of not requiring immediate access to specialist equipment and expertise. Blood samples are activated, fixed, stored, and transported to a central laboratory for flow cytometric analysis. Here we have compared P-selectin with other more traditional approaches to measuring platelet function in blood and/or platelet-rich plasma (PRP) from patients with acute coronary syndromes on treatment for at least 1 month with either aspirin and clopidogrel or aspirin with prasugrel. The comparators were light transmission aggregometry (LTA), VerifyNow and Multiplate aggregometry (for determining the effects of aspirin) and LTA, VerifyNow and Multiplate together with the BioCytex VASP phosphorylation assay (for the P2Y12 antagonists). The P-selectin Aspirin Test revealed substantial inhibition of platelet function in all but three of 96 patients receiving aspirin with clopidogrel and in none of 51 patients receiving aspirin and prasugrel. The results were very similar to those obtained using LTA. There was only one patient with high residual platelet aggregation and low P-selectin expression. The same patients identified as "non-responders" to aspirin also presented with the highest residual platelet activity as measured using the VerifyNow system, although not quite as well separated from the other values. With the Multiplate test only one of these patients clearly stood out from the others. The results obtained using the P-selectin P2Y12 Test in 102 patients taking aspirin and clopidogrel were similar to the more traditional approaches in that a wide scatter of results was obtained. Generally, high values seen with the P-selectin P2Y12 Test were also high with the LTA, VerifyNow, Multiplate, and BioCytex VASP P2Y12 Tests. Similarly, low residual platelet function using the P2Y12 test was seen irrespective of the testing procedure used. However, there were differences in some patients. Prasugrel was always more effective than clopidogrel in inhibiting platelet function with none of 56 patients (P-selectin and VerifyNow), only 2 of 56 patients (Multiplate) and only 3 of 56 patients (Biocytex VASP) demonstrating high on-treatment residual platelet reactivity (HRPR) defined using previously published cut-off values. The exception was LTA where there were 11 of 56 patients with HRPR. It remains to be seen which experimental approach provides the most useful information regarding outcomes after adjusting therapies in treated patients.